2017
DOI: 10.1007/s00787-017-1074-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of hair pulling disorder and excoriation disorder in Tourette syndrome

Abstract: Trichotillomania/hair pulling disorder (HPD) and excoriation/skin picking disorder (SPD) are childhood-onset, body-focused repetitive behaviors that are thought to share genetic susceptibility and underlying pathophysiology with obsessive-compulsive disorder (OCD) and Tourette syndrome (TS). We sought to determine the prevalence of DSM-5 HPD and SPD in TS patients, and to identify clinical factors most associated with their co-morbidity with TS. Participants included 811 TS patients recruited from TS specialty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…57 In this same multivariable analysis, comorbid OCD was not associated with occurrence of TTM in TS patients. 57 Finally, we found that between 2.6 and 20% of TTM patients had a history of OCD, 49,53,[59][60][61][62] while 0 to 3% had a history of tic disorders. 53,60 When comparing tic comorbidity in OCD and TTM patients, five studies reported that TTM patients have the same level of tic disorders as OCD patients.…”
Section: Comorbiditymentioning
confidence: 75%
See 4 more Smart Citations
“…57 In this same multivariable analysis, comorbid OCD was not associated with occurrence of TTM in TS patients. 57 Finally, we found that between 2.6 and 20% of TTM patients had a history of OCD, 49,53,[59][60][61][62] while 0 to 3% had a history of tic disorders. 53,60 When comparing tic comorbidity in OCD and TTM patients, five studies reported that TTM patients have the same level of tic disorders as OCD patients.…”
Section: Comorbiditymentioning
confidence: 75%
“…67 These studies highlight a relationship between tics and TTM, not only in an OCD context (and, possibly, in the specific context of early-onset OCD 7,54 ), but also directly in TS patients. 57 This last study helps us reach the conclusion that the TTM-tic relationship seems stronger than the TTM-OCD relationship, since OCD was not associated with occurrence of TTM in TS patients.…”
Section: Comorbiditymentioning
confidence: 77%
See 3 more Smart Citations